Near Eastern Precedents of the “Orphic” Gold Tablets: The Phoenician Missing Link - López-Ruiz, Carolina (Journal of ancient Near Eastern religions, 2015)
The Greek Gold Tablets (also called “Orphic Gold Tablets”), have often been compared with Egyptian funerary texts, especially those comprising the Book of the Dead. At the same time, North-West Semitic gold and silver leaves (Phoenician-Punic and Hebrew) with protective formulae offer a close parallel to them in aspects of their function and form. Although this group of funerary amulets are also said to follow Egyptian models, the three corpora have never been discussed together. Egyptian afterlife motifs and magical technologies may have indirectly influenced Greek Orphic funerary ideas and practices. I suggest, however, that this transmission happened through adaptations of Egyptian materials in the Phoenician-Punic realm, with evidence pointing to southern Italy and Sicily (Magna Graecia) as likely scenarios for this exchange. Intersections between Orphic and Phoenician cosmogony and the selective use of Egyptian iconography in Phoenician funerary amulets reinforce this hypothesis.